Hubungan Kecerdasan Logika Matematika dan Motivasi Berprestasi dengan Pemahaman Konsep Statistika pada Siswa Madrasah Aliyah Se-Kabupaten Grobogan - Masudi Masudi; Muhammad Akhyar; Akhmad Arif Musadad (Universitas Sebelas Maret, 2017)
This research aims to find out: (1) correlation of logical mathematic intelligence and understanding of statistic concept, (2) correlation of motivation and understanding of statistic concept, and (3) correlation of logical mathematic inteligence and motivation simultaneously with statistic concept understanding of Madrasah Aliyah students of Grobogan district in 2015/2016 academic year. This research was correlational research, which aimed to find out the correlation independent variable of logical mathematic intelligence and motivation with dependent of understanding of statistic concept. The population were all of Madrasah Aliyah students in grobogan district in 2015/2016 academic year with total of 110 students were selected as sample. They are 58 students of Madrasah Aliyah Suniyyah Selo, 32 Students of Madrasah Aliyah Nuril Huda, and 20 Students of Madrasah Aliyah Miftahut Thulab. The analysis data used simple regression and double regression analysis. Based on the results of this research, it can be concluded that: (1) logical mathematic intelligence and understanding of statistic concept of students of Madrasah Aliyah in grobogan district have a significant positive correlation, (2) motivation and understanding of statistic concept of students of Madrasah Aliyah in grobogan district have no significant positive correlation (3) Logical mathematic intelligence and motivation have a significant positive correlation simultananeously with statistic concept understanding of Madrasah Aliyah students in Grobogan district.